2011
DOI: 10.1128/jb.01076-10
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Burkholderia cepacia UDP-Glucose Dehydrogenase (UGD) BceC and Role of Tyr10 in Final Hydrolysis of UGD Thioester Intermediate

Abstract: Members of the Burkholderia cepacia complex (BCC) are serious respiratory pathogens in immunocompromised individuals and in patients with cystic fibrosis (CF). They are exceptionally resistant to many antimicrobial agents and have the capacity to spread between patients, leading to a decline in lung function and necrotizing pneumonia. BCC members often express a mucoid phenotype associated with the secretion of the exopolysaccharide (EPS) cepacian. There is much evidence supporting the fact that cepacian is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…(D,E)]. Both 3g79A and 2y0cA consist of two dinucleotide binding Rossmann‐like folds in the N‐ and C‐terminal domains, where the subtle difference in the intermediate linker domain results in a small twist on the domain orientation . However, the I‐TASSER potential was unable to distinguish the domain orientations where nearly equal numbers of the structure decoys have been generated by the I‐TASSER simulations, for the different domain orientations, as indicated by the similar rank of consensus score shown in Table .…”
Section: Resultsmentioning
confidence: 95%
“…(D,E)]. Both 3g79A and 2y0cA consist of two dinucleotide binding Rossmann‐like folds in the N‐ and C‐terminal domains, where the subtle difference in the intermediate linker domain results in a small twist on the domain orientation . However, the I‐TASSER potential was unable to distinguish the domain orientations where nearly equal numbers of the structure decoys have been generated by the I‐TASSER simulations, for the different domain orientations, as indicated by the similar rank of consensus score shown in Table .…”
Section: Resultsmentioning
confidence: 95%
“…This helix also contributes to intersubunit contacts responsible for formation of homodimers, as seen in PaGDPMDH (Fig. B) and Burkholdaria cepacia UDPGDH . Motif 2 contains the fully conserved residues Gly257{408}, Gly258{409}, Cys260{411} and Asp264{415}.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the distribution of fluorescence is similar in all cases. As a negative control, we conducted a colocalization experiment using BceC, an intracellular Burkholderia enzyme involved in exopolysaccharide synthesis (Rocha et al, ). The Pearson's correlation coefficient (Rr; 0.124 for x – y plane and 0.177 for side view; Figure S3) was significantly lower than the one determined for the pair TNFR1‐BcaA, validating our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the distribution of fluorescence is similar in all cases. As a negative control, we conducted a colocalization experiment using BceC, an intracellular Burkholderia enzyme involved in exopolysaccharide synthesis (Rocha et al, 2011).…”
Section: Colocalization Of Bcaa With Tnfr1 In Human Bronchial Epithmentioning
confidence: 99%